Response of Broiler Chickens to Dietary Supplementation of Enzymatically Hydrolyzed Glucan or Mannan Yeast Products. (9th May 2019) - Ahiwe, E U; Omede, A A; Abdallh, M E; Chang'a, E P; Al-Qahtani, M; Gausi, H; Graham, H; Iji, P A
SUMMARY: The effect of varying levels of enzymatically hydrolyzed soluble yeast glucan (YG) and yeast mannan (YM) products on broiler chickens was studied. A total of 486 day-old male Ross 308 broiler chicks were allocated to 9 dietary treatments consisting of YG and YM supplemented at 0.05, 0.10, 0.15, or 0.20 g/kg diet, respectively, and a control without yeast supplementation. Each treatment was replicated 6 times with 9 birds per replicate. The supplements did not affect body weight gain (BWG) and feed conversion ratio (FCR) in the starter phase nor feed intake at any stage. However, birds especially in the 0.20 g YM/kg diet group had improved ( P < 0.05) BWG and FCR than the other groups over 0–24 d and 0–35 d. There were no treatment effects on visceral organ weight at 10 d, but the small intestine was heavier ( P < 0.05) in the 0.20 g YM/kg diet group compared to others at 24 d. Broilers fed 0.15 or 0.20 g YM/kg diet had a significantly ( P < 0.05) higher ileal protein digestibility than the control group. Total protein and endogenous enzyme activities were not affected by the supplements. On 35 d, the dressing percentage of broiler carcass and breast weight was significantly ( P < 0.05) improved by 0.20 g YM/kg diet. The results from this study confirm the usefulness of YM at 0.15 or 0.20 g/kg diet performance and may be beneficial in improving productivity for broiler chicken farmers.